THE INFLUENCE OF TEACHER TEACHING METHODS AND LEARNING MOTIVATION ON THE LEARNING OUTCOMES OF IPS SUBJECTS OF SENIOR HIGH SCHOOL MAMBAUS SHOLIHIN STUDENTS SUCI MANYAR GRESIK - Mahfudz Sulaiman; Nurul Huda (Universitas Islam Zainul Hasan Genggong, 2024)
In general, this study aims to determine the effect of teaching methods teachers and motivation to learn the results of learning subjects IPS MA students. Mambaus Shoihin Suci Manyar Gresik. Specifically the purpose of this study are (1) Describe the influence of teaching methods teachers to the results of learning subjects IPS Senior High School students. Mambaus Shoihin Suci Manyar Gresik. (2) Describe the influence of learning motivation on learning outcomes ips subjects students MA. Mambaus Shoihin Suci Manyar Gresik. (3) Describe the influence of together teaching methods of teachers and learning motivation on the learning outcomes subjects IPS students MA. Mambaus Sholihin Suci Manyar Gresik. The population in this study were Senior High School students. Mambaus Shoihin Suci Manyar Gresik academic year 2016/2017 which then taken a sample of 33 students. The data of research about teaching method of teacher and learning motivation is obtained through questionnaire method by using likert scale and student learning result data on IPS subjects obtained from semester 1. Next data is analyzed by using multiple regression technique with computer assistance program of SPSS For Windows version 11.5. From multiple linear regression analysis test